1993
DOI: 10.1016/s0006-3495(93)81273-6
|View full text |Cite
|
Sign up to set email alerts
|

Microspectrofluorometry of the protonation state of ellipticine, an antitumor alkaloid, in single cells

Abstract: The protonation state and intracellular distribution of ellipticine were investigated in single human mammary T47D cells by confocal laser microspectrofluorimetry. In the cell nucleus, only the protonated form of ellipticine was detected as a direct consequence of its apparent pK increase upon DNA binding. Both protonated and neutral forms were present in the aqueous cytoplasm, where the pH is close to the drug pK. When cells were incubated in high concentrations of K+, a condition that depolarizes the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 24 publications
5
42
0
Order By: Relevance
“…DIMIQ, possessing simultaneously at this pH the neutral and anionic forms, binds to a substantially larger extent (up to 45%). As reported by Sureau et al 43) in the presence of neutral micelles or liposomes, the pK a of ellipticine was reduced, as a result of reduced polarity at the interface. The same mode of action is presumably present in our experiment.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…DIMIQ, possessing simultaneously at this pH the neutral and anionic forms, binds to a substantially larger extent (up to 45%). As reported by Sureau et al 43) in the presence of neutral micelles or liposomes, the pK a of ellipticine was reduced, as a result of reduced polarity at the interface. The same mode of action is presumably present in our experiment.…”
Section: Resultssupporting
confidence: 60%
“…Moreover, the increase of pK a should also be considered as a consequence of increased proton activity at the anionicwater interface, as observed for ellipticine. 43,44) Binding to the membranes, apart from the hemolytic effect, as will be discussed below, can cause an increase in membrane surface area and therefore osmotic fragility. Overall, observations with hydrophobic model systems might suggest that the protonation equilibrium of tested chemicals can be shifted in response to its interactions with different biological macromolecules in vivo as a consequence of the local pH environment.…”
Section: Resultsmentioning
confidence: 99%
“…This radical not only tremendously improves the hydrophilicity of the compound, allowing rapid cellular uptake, but also prevents intracellular metabolism by the hydroxylation at C-9 of ellipticine (14). Although initially categorized as a topo II inhibitor that localizes to the nucleus, ellipticine has more recently been shown to localize in the cytoplasm and accumulate in mitochondria (26). Similarly, EPED3, which displays intrinsic fluorescence identical to ellipticine, was found to rapidly accumulate in the mitochondria in this study.…”
Section: Discussionsupporting
confidence: 52%
“…Tetraphenylphosphonium (TPP ϩ ) was purchased from Merck. Mitochondria Isolation-Rat liver mitochondria from male Wistar albino rats were isolated by differential centrifugation as described previously (6).…”
Section: Methodsmentioning
confidence: 99%
“…However, good evidence lacks when it comes to correlating in vivo activities with a specific DNA binding mode (5). Data based on microspectrofluorometric analyses have shown that an important fraction of ellipticine accumulates in mitochondria (6). The possibility that these organelles rather than the nucleus might be a privileged pharmacological target has been suggested.…”
mentioning
confidence: 99%